Characterization of Copaifera reticulata Ducke morphotypes and their correlation with soil chemical quality attributes (Research, Society and Development, 2022)
The morphological characterization of a species contributes to better identification of morphotypes, in addition to supporting the production of food, herbal and aesthetic condiments. In the Copaifera genus, among the different species, Copaifera reticulata Ducke has morphotypes that need to be characterized in order to be better utilized and conserved. In this sense, the work aimed to identify and morphologically characterize the bark of individuals of Copaifera reticulata, through anatomical description and to correlate them with edaphic characteristics, in a managed forest area, located in the municipality of Moju, Pará. The research was carried out at the São Roque Agroecological Farm, Moju, PA, where, for the identification and characterization of the bark, 10 individuals were selected, which were collected samples of bark (14 cm long x 10 cm wide) and analyzed the variables, shape tree stem, bark color, bark surface, presence or absence of lenticels, depressions, streaks, loosening of plates, cracks and presence or absence of thorns and fungi in the bark. For the correlation of the bark with the edaphic characteristics, the soil was collected and the variables MO (g/Kg), pH (water), P, K, Na, Ca, Ca+Mg and H + Al were analyzed. The results showed that the MO (g/Kg), pH (water), K, Ca, Ca+Mg and H + Al variables were correlated with C. reticulata tree bark, while the P and Na variables were not correlated with any variable related to the bark of individuals from Copaiba. It is concluded that there was a difference between individuals of C. reticulata, based on morphological characteristics of the bark, serving to identify and characterize morphotypes within the species, as well as the morphotypes of copaiba were influenced by the edaphic characteristics of the growth site of the trees, existing a correlation.